Testing and validating a disaster mutual assistance decision support tool for electricity companies. (2017) - Asgary, Ali; Nosedal-Sanchez, Jenaro; Pantin, Ben; Wu, Jianhong; Sabet, Maryam Shafiei
Recent large-scale electricity disruptions in North America like the 2013 ice storm and hurricane Sandy (2012) highlighted the merits of mutual assistance as a disaster recovery and continuity mechanism. The decision to provide assistance requires careful consideration of multiple factors in a timely manner. This paper examines and tests the validity and reliability of a disaster mutual assistance decision support tool that is being developed for Canadian electricity companies using a multi-criteria decision method and simulation tools. Participating experts from utility companies were provided with a number of mutual assistance scenarios and their decisions to provide assistance with and without using the decision support tool were analysed. Findings show that the decisions suggested by the tool are consistent with experts' decisions and this tool has the potential to inform decisions during mutual assistance operations.